2019
DOI: 10.2174/1573399815666190115144534
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Interrelationship of Diabetes and Periodontium

Abstract: : Periodontitis is a chronic inflammatory disease characterised by destruction of the supporting structures of the teeth which is a common cause of tooth mortality in all individuals throughout the world. Diabetes is a group of metabolic dysregulation, primarily of carbohydrate metabolism, characterized by hyperglycemia that results from defects in insulin secretion, impaired insulin action, or both. Systematic reviews and meta-analysis have shown that the prevalence of periodontitis is increased in diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In our study, both RANKL and OPG showed increased values when compared to non-diabetics both pre- and post-extraction. Another study analyzing these variations in gingival crevicular fluid highlighted that RANKL levels and RANKL/OPG ratio is higher in poorly controlled diabetics with chronic periodontitis, compared to healthy individuals but also subjects with diabetes with optimal metabolic control and periodontitis, and this ratio was not significantly affected by periodontal therapy [ 19 ]. Thus, our study strengthens the belief that the RANKL/OPG ratio is negatively influenced in diabetes, especially in subjects with poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both RANKL and OPG showed increased values when compared to non-diabetics both pre- and post-extraction. Another study analyzing these variations in gingival crevicular fluid highlighted that RANKL levels and RANKL/OPG ratio is higher in poorly controlled diabetics with chronic periodontitis, compared to healthy individuals but also subjects with diabetes with optimal metabolic control and periodontitis, and this ratio was not significantly affected by periodontal therapy [ 19 ]. Thus, our study strengthens the belief that the RANKL/OPG ratio is negatively influenced in diabetes, especially in subjects with poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic diseases closely related to PD include type 2 diabetes, thrombosis, arteriosclerosis, bacterial endocarditis, aspiration pneumonia, cancer, arthritis, and osteoporosis [6,7]. Disease control in patients with systemic diseases is more challenging when they also have PD, which adversely affects quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients with severe periodontitis have six times more insufficient glycemic control (hyperglycemia) than patients with healthy periodontium, leading to exaggerated immune-inflammatory responses induced by periodontal pathogens. However, improved glycemic control reduces the severity of periodontal disease ( Badiger et al, 2019 , Wu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%